Personal responsibility for health? A phenomenographic analysis of general practitioners' conceptions - Joar Björk; Terese Stenfors; Niklas Juth; A. Birgitta Gunnarsson (Taylor & Francis Group, 2021)
Objective To analyse and describe general practitioners' perceptions of the notion of a 'personal responsibility for health'. Design Interview study, phenomenographic analysis. Setting Swedish primary health care. Subjects General Practitioners (GPs). Main outcome measures Using the phenomenographic method, the different views of the phenomenon (here: personal responsibility for health) were presented in an outcome space to illustrate the range of perceptions. Results The participants found the notion of personal responsibility for health relevant to their practice. There was a wide range of perceptions regarding the origins of this responsibility, which was seen as coming from within yourself; from your relationships to specific others; and/or from your relationship with the generalized other. Furthermore, the expressions of this responsibility were perceived as including owning your health problem; not offloading all responsibility onto the GP; taking active measures to keep and improve health; and/or accepting help in health. The GP was described as playing a key role in shaping and defining the patient's responsibility for his/her health. Some aspects of personal responsibility for health roused strong emotions in the participants, especially situations where the patient was seen as offloading all responsibility onto the GP. Conclusion The notion of personal responsibility for health is relevant to GPs. However, it is open to a broad range of interpretations and modulated by the patient-physician interaction. This may make it unsuitable for usage in health care priority settings. More research is mandated to further investigate how physicians work with patient responsibility, and how this affects the patient-physician relationship and the physician's own well-being.Key Points The notion of personal responsibility for health has relevance for discussions about priority setting and person-centred care. This study, using a phenomenographic approach, investigated the views of Swedish GPs about the notion of personal responsibility for health. The participants found the notion relevant to their practice. They expressed a broad range of views of what a personal responsibility for health entails and how it arises. The GP was described as playing a key role in shaping and defining the patient's responsibilities for his/her health. The notion was emotionally charged to the participants, and when patients were seen as offloading all responsibility onto the GP this gave rise to frustration.